Captive offshoring drivers in the manufacturing industry: criteria and sub-criteria that influence the location choice. Issue 1 (2nd January 2021) - De Felice, Fabio; Petrillo, Antonella; Petrillo, Laura
Abstract : Captive offshoring is one of the most strategic approach in complex, dynamic and competitive global supply chains. In the present research, a rigorous decision-making model to identify captive offshoring drivers, that play a role in the company strategy and limiting the subjectivity of human decisions, has been proposed. Firstly, the Delphi method has been used to investigate and to identify criteria and sub-criteria that influence the captive offshoring strategy. Then, the Fuzzy Analytic Hierarchy Process (FAHP) method has been employed to calculate the weight of importance of each criteria and sub-criteria. The purpose of this paper is to address the relevance of strategic capabilities for the operation of international manufacturing to the captive offshoring decision. A real case study on captive offshoring concerning an Italian manufacturing company has been analysed. This study adds to the limited number of studies on the identification of captive offshoring drivers and contributes to the quantitative research on this topic. From a practical perspective, the research highlights that multi-criteria decision methods are well indicated to select criteria and sub-criteria that influence the location choice. The result will help managers to make specific decisions concerning their current captive offshoring policy.